Results of a Community Randomized Study of a Faith-Based Education Program to Improve Clinical Trial Participation among African Americans - Frew, Paula M. (Int J Environ Res Public Health, 2015)
This is a report of a cluster randomized clinical trial evaluating the effectiveness of a church-based educational intervention aimed at improving African Americans’ (AA) participation in clinical trials. Two hundred and twenty-one AA subjects ages ≥50 years from six predominantly AA churches were randomized to intervention or control condition. The intervention included three educational sessions about clinical trials and health disparities; control participants completed questionnaires. Primary endpoints of the study were differences in individual subjects' intentions to obtain clinical trial information and intention to join a clinical trial, as determined by 10 point scale items at baseline, three and six months. A statistically significant increase in the intention to obtain clinical trial information at the three and six month time points was observed in the intervention group, but not the control group. Older participants (65–95 years) were less likely than younger participants (50–64 years) to increase their motivation to seek clinical trial information by the three and six month time points. No significant increases were observed in intention to join clinical trials. This randomized trial shows that AA church-based educational interventions are likely to increase the motivation of AA subjects to obtain clinical trial information and are therefore potentially effective at ameliorating the underrepresentation of AA subjects in clinical trials.